Strong-coupling theory of condensate-mediated superconductivity in two-dimensional materials - Meng Sun; A. V. Parafilo; V. M. Kovalev; I. G. Savenko (Physical Review Research, 2021)
We develop a strong-coupling theory of Bose-Einstein condensate-mediated superconductivity in a hybrid system, which consists of a two-dimensional electron gas with either: (i) parabolic spectrum or (ii) relativistic Dirac spectrum in the vicinity of a two-dimensional solid-state condensate of indirect excitons. The Eliashberg equations are derived, and the expressions for the electron pairing self-energy due to the exchange interaction between electrons mediated by a single Bogoliubov excitation (a bogolon) and the bogolon pairs are found. Furthermore, we find the superconducting order parameter and estimate the critical temperature of the superconducting transition. The critical temperature reveals its linear dependence on the dimensionless coupling constant. It is shown that the bogolon-pair-mediated interaction is the dominant mechanism of electron pairing in hybrid systems in both the weak- and the strong-coupling regimes. We calculate the effective bogolon-electron interaction constant for both parabolic and linear electron dispersions and examine the dependence of the critical temperature of the superconducting transition on exciton condensate density.